Determinasi Minat Pembelian Mobil Listrik Pasca Insentif Pajak di Indonesia: Integrasi Customer-Based Brand Equity dan Theory of Planned Behavior - Daniel Aditama (Jurnal Locus Penelitian dan Pengabdian, 2026)
The termination of several electric vehicle (EV) fiscal incentives in Indonesia in 2026, may dampen consumer purchase intention, as evidenced by market shocks in Denmark and China. This study analyzes the determinants of EV purchase intention in Indonesia by integrating Customer-Based Brand Equity (CBBE) and Theory of Planned Behavior (TPB) frameworks, while examining the moderating roles of perceived price and tax incentives. Using a quantitative explanatory approach with purposive sampling, data were collected from 430 respondents in Greater Jakarta who are existing EV owners. Data analysis employed Partial Least Squares Structural Equation Modeling (PLS-SEM). Of nineteen hypotheses tested, eighteen were supported, with an R-square of 0.830 for purchase intention. The three TPB determinants and four CBBE dimensions significantly influence purchase intention, with brand loyalty emerging as the strongest predictor. Perceived price moderates the attitude and purchase intention pathway, while tax incentives only moderate the subjective norms and perceived behavioral control pathways.